An Investigation of Using Think Talk Write Strategy to Enhance Writing Procedure Text - Siahaan, Mungkap Mangapul; Sirait, Setia Oktaviana; Nababan, Irene Adryana (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to investigate the effect of using the Think Talk Write Strategy on the writing procedure text capability of eleventh-grade students at vocational SMK GKPI 1 Pematangsiantar. This research used a quasi-experimental research design. The population of this study was the eleventh-grade students of vocational SMK GKPI 1 Pematangsiantar, and the total number of students was 216. The sample of this study was divided into two classes: the experimental class was (XI KW), consisting of 27 students who used the Think Talk Write strategy, and the control class (XI TJTL) was composed of 27 students who only used the cturing strategy. The data collection instruments used writing tests for the pre-test and post-test. Brown’s writing assessment rubric was used in this research, and it included content, organization, grammar, vocabulary, and mechanics. SPSS 26 Version was used to analyze the data by conducting descriptive analysis, normality test, Wilcoxon test, homogeneity test, and Mann-Whitney test. The data analysis using the Mann-Whitney test showed that the Assymp. Sig (2-tailed) value of 0.007< 0.05. Based on these findings, Ha is accepted, and Ho is rejected. Therefore, it can be concluded that The ink Talk Write Strategy significantly affected the writing procedure text capability of the eleventh-grade students at vocational SMK GKPI I Pematangsiantar.